Processing and Characterization of Acrylonitrile Butadiene Styrene (ABS)-Based Biocomposite Filaments Reinforced with Oil Palm Empty Fruit Bunch - Handika Dany Rahmayanti; Rakha Amanta Pradipa; Nurul Akmalia; Haryasena Gusti Andayu (Postgraduate, University of Mataram, 2026)
The growing demand for sustainable materials in additive manufacturing has driven interest in biocomposite filaments reinforced with natural fillers. In this study, ABS-based biocomposite filaments reinforced with oil palm empty fruit bunch (OPEFB) microfibrillated cellulose were successfully fabricated using a single-screw extrusion process. The OPEFB cellulose content was varied from 0 to 30 wt.% to evaluate its effect on filament dimensional stability, morphology, and chemical structure. Filament extrusion was performed at a processing temperature of 220 °C and an extrusion speed of 850 to ensure stable melt flow and minimize thermal degradation. The results show that the filament diameter remained relatively stable within the range of 2.50-2.80 mm across all compositions, indicating good dimensional control during extrusion. This study highlights the novelty of successfully fabricating ABS-based biocomposite filaments reinforced with OPEFB microfibrillated cellulose using a simple process. SEM analysis revealed that low OPEFB content (2 wt.%) resulted in uniform filler dispersion and good interfacial bonding, while higher filler loadings led to increased porosity, agglomeration, and surface roughness, which may adversely affect filament quality and printability. The current findings demonstrate that OPEFB can enhance filament characteristics even at low composition scales. The presented results are comprehensive enough for initial filament characterization, including dimensional stability, morphology, and chemical structure, which adds to the interest of this study and has not been previously presented. FTIR analysis confirmed that no chemical modification occurred between the ABS matrix and OPEFB cellulose, with interactions dominated by physical bonding. Overall, the findings demonstrate that ABS-OPEFB biocomposite filaments with low to moderate cellulose content can be effectively produced and show potential for fused deposition modeling applications, offering a sustainable alternative to conventional ABS filaments.